Influence of thermal shocks on the He induced surface morphology on tungsten. (January 2019) - Hamaji, Y.; Tokitani, M.; Kreter, A.; Sakamoto, R.; Sagara, A.; Tamura, H.; Masuzaki, S.
Highlights: The effects of thermal shocks on He induced surface morphology on tungsten was investigated. He induced morphologies such as undulations and holes were collapsed by ELM-like thermal shocks. The results suggests that the timerange of ELM-like thermal shock is enough long to change He induced surface morphology. Abstract: In this study, the effect of ELM-like thermal shocks on He induced surface morphology were investigated. A W sample was exposed to pure He plasma. He ion incident energy, flux and fluence were 80 eV, 1 × 10 22 /m 2 /s and 3 × 10 25 /m 2, respectively. Irradiation temperature were approximately 470 and 1100 K. Then, thermal shocks were applied on the sample using focused electron beam. The peak heat flux, pulse duration and base temperature were 500 MW/m 2, 500 μs and R.T., respectively. After the thermal shocks, He induced morphologies such as holes and periodic undulations were flatten completely at the region exposed to the highest heat flux. At the peripheral regions of the electron beam spot, the hole density increase or partial flattening of morphologies were observed. These results suggested that in order to anticipate surface morphology with He irradiation and ELMs, the peak temperature should play a more important role than base temperature.